PENGARUH KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019) - Teguh Erawati; Amalia Putri Ramadhani (Fakultas Ekonomi UNIBBA, 2021)
The purpose of this study was to examine the effect of dividend policy and profitability on firm value with good corporate governance as a moderating variable. This research was conducted at manufacturing companies listed on the IDX in 2015-2019. The population in this study amounted to 178 companies. The sample was selected using a purposive sampling method so that the number of samples was 27 companies. The analysis technique used in data testing is Moderated Regression Analysis (MRA), and it is processed using the IBM SPSS 20 software. The results showed that dividend policy and profitability had a positive and significant effect on firm value.Managerial ownership weakens the positive relationship between dividend policy on firm value but strengthens the positive relationship between profitability and firm value. Managerial ownership weakens the positive relationship between dividend policy and profitability on firm value